THE IMPACT OF WORK-LIFE BALANCE, ORGANIZATIONAL COMMITMENT, AND REWARDS ON TURNOVER INTENTION: A STUDY OF ONLINE TRANSPORTATION DRIVING PARTNERS IN INDONESIA - Marhaeni, Novie Prasetyaning; Waliah, Siti; Isha, Ahmad Shahrul Nizam Bin; Nirmala, Isma (SULTANIST: Jurnal Manajemen dan Keuangan, 2025)
The phenomenon of high rates of driver-partner migration from one platform to another is an important concern for application-based transportation service providers. This study aims to analyze the impact of work-life balance, organizational commitment, and rewards on turnover intention in online transportation driver-partners in Indonesia. Quantitative methods were used in this study by collecting data through questionnaires to 150 driver-partners from various major cities in Indonesia. Data were analyzed using multiple linear regression techniques to determine the effect of each independent variable on turnover intention. The results of the study indicate that work-life balance, organizational commitment, and rewards have a significant positive and significant effect on turnover intention, meaning that the better the balance of work, organizational commitment and personal life and the incentives received by drivers, the lower their desire to leave the platform. These findings provide practical implications for online transportation service providers to design driver-partner retention strategies with a focus on improving work welfare and providing appropriate rewards, in order to create a more stable and sustainable working relationship